Integration of the Qur'an and Science About the Process of Human Creation: Integrasi al-Qur’an dan Sains Tentang Proses Penciptaan Manusia - Farihah, Anis (Journal of Islamic and Muhammadiyah Studies, 2023)
According to al-Qur'an, humans were created from the earth with various kinds of process derivatives, even revealed in the Qur'an that not only involves land, but also includes water. So the formulation of the problem in this study is: What is the process of human creation according to the Qur'an and Modern Science? This research is a qualitative study using pure literature study that utilizes the Qur'an as the main reference book and supporting book of commentaries and several websites that correlate with the title. The process of human creation in the Qur'an is divided into 4 models. First, the creation of the Prophet Adam AS; second, the creation of Eve; third, the creation of the Prophet Isa. fourth, human creation in general. Thus the creation of humans according to science is integrated with the Qur'an Surah al-Mukminun verses 12-14 which is included in the fourth model of human creation in the Qur'an.